Thoracodorsal nerve transfer for triceps reinnervation in partial brachial plexus injuries. Issue 3 (29th January 2015) - Soldado, Francisco; Ghizoni, Marcos F.; Bertelli, Jayme
Abstract : Purpose: To report the clinical outcomes of thoracodorsal nerve (TDN) transfers to the triceps motor branches for elbow extension restoration in patients with partial brachial plexus injuries (BPI). Methods: Eight male patients of mean age 23 years and suffering from a partial BPI underwent direct coaptation of the TDN to the nerve of the upper medial and long heads of the triceps, an average 6 months after their accident. Results: Seven patients achieved M4 elbow extension strength and one patient M3, according to the BMRC scale, after a mean follow‐up of 21 months. Discussion: Direct TDN transfer might be a valid surgical procedure for the restoration of elbow extension in patients with partial BPI. © 2015 Wiley Periodicals, Inc. Microsurgery 36:191–197, 2016.